Breast Cancer Metastasis to the Stomach That Was Diagnosed after Endoscopic Submucosal Dissection. (9th November 2016) - Kita, Masahide; Furukawa, Masashi; Iwamuro, Masaya; Hori, Keisuke; Kawahara, Yoshiro; Taira, Naruto; Nogami, Tomohiro; Shien, Tadahiko; Tanaka, Takehiro; Doihara, Hiroyoshi; Okada, Hiroyuki
Abstract : A 52-year-old woman presented with stage IIB primary breast cancer (cT2N1M0), which was treated using neoadjuvant chemotherapy (epirubicin, cyclophosphamide, and paclitaxel). However, the tumor persisted in patchy areas; therefore, we performed modified radical mastectomy and axillary lymph node dissection. Routine endoscopy at 8 months revealed a depressed lesion on the gastric angle's greater curvature, and histology revealed signet ring cell proliferation. We performed endoscopic submucosal dissection for gastric cancer, although immunohistochemistry revealed that the tumor was positive for estrogen receptor, mammaglobin, and gross cystic disease fluid protein-15 (E-cadherin-negative). Therefore, we revised the diagnosis to gastric metastasis from the breast cancer.